1997
DOI: 10.1161/01.atv.17.11.2692
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Rheological and Hemostatic Parameters and Acute-Phase Reactants in Young, Healthy Subjects

Abstract: The incidence of cardiovascular diseases is increased in winter months. Recent studies have shown seasonal changes in plasma viscosity, fibrinogen, and factor VII activity with elevated levels during winter. An increase in these factors generates a "hypercoagulable state," which may lead to a rise in cardiovascular morbidity and mortality. It has been suggested that an increase in upper respiratory infections might be the underlying cause for the raised acute-phase reactants, in particular fibrinogen, during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 48 publications
4
48
1
1
Order By: Relevance
“…These findings are difficult to explain. It cannot be excluded that seasonal variations in morphological and biochemical blood parameters influenced the cited results (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are difficult to explain. It cannot be excluded that seasonal variations in morphological and biochemical blood parameters influenced the cited results (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…FR_HLICH et al 1997 shown seasonal changes in fibrinogen where maximum level was reached in April, and the seasonal difference was 0,32 g/L.…”
Section: Discussionmentioning
confidence: 96%
“…This phenomenon is difficult to explain. Perhaps it resulted from the fact that our winter swimmers were well-trained or have been actively involved in other sports disciplines, such as jogging, cycling, kayaking, trekking and swimming both of them may affect deformability of erythrocytes at $1.13 Pa. FR_HLICH et al (1997) indicated that RBC deformability undergoes large seasonal changes, with the peak level in November (14.5 AU) and the lowest level in April (13.1 AU) (P<001).…”
Section: Discussionmentioning
confidence: 98%
“…A legnagyobb mértékű változást a plazma fi brinogénkoncentrációja mutatja, amely alacsony légköri hőmérsékleten 23%-os emelkedéssel bír [20]. A plazmaviszkozitás maximális szintjét január hónapra teszik [21,22]. A vérnyomás szintén emelkedő értéket mutat [23,24,25].…”
Section: Eredeti Közleményunclassified